IMPLEMENTATION OF MURABAHAH AGREEMENTS TO MEET CUSTOMERS' NEEDS REGARDING THE BUYING OF BAITUT TAMKIN LUMBUNG BERSAING - Lia Idayani (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2023)
In this research approach, the author uses a qualitative approach, as for the reason the researcher uses this qualitative approach, it is hoped that the researcher will obtain as much information as possible in the form of concepts, information, impressions and responses to the problems that the researcher is studying so that a clear picture of the Implementation of the Murabah Agreement in Meeting Needs will be seen. Customers Regarding the Buying and Selling of Goods (BTLB Aikmel Unit Case Study. The author can conclude that the implementation of Murabahah financing at Baitut Tamkin, Baitut Tamkin acts as the party that provides financing in the form of goods and members submit applications for financing in purchasing goods. Murabahah products are financing products that most popular with members, where in implementing the Murabahah contract the transaction process is also easier for members to understand, and Baitut Tamkin facilitates financing in buying and selling goods provided to members. Financing carried out at Baitut Tamkin in the form of purchasing goods for members is multi-purpose goods such as (electronic goods, household equipment, procurement of merchandise, basic necessities, raw materials) which do not conflict with Islamic Sharia, for this reason members associated with Baitut Takin. The forms of contracts and convenience in the stages of the financing process provided by Baitut Tamkin to meet members' needs are: Baitut Tamkin provides financing for goods desired by members, Baitut Tamkin purchases the types of goods desired by members, Payment for goods is made in installments in accordance with mutual agreement.